Strategi Pemasaran Produk Hasil Olahan Desa Ngloro Kecamatan Saptosari Kabupaten Gunungkidul DIYogyakarta - Incharisma, Maria; Simbolon, Angelita Rogabe T; Tabita, Skolastika Gadis; Christine, Christine; Kusumatriawan, Ardhiel Junico A; Beraya, Fransiska Millenia A L B; Ardhiawan, Nicolas Raditya; Hananta, Juninho Yudistira; Pangestuti, Patricia Aurelia U; Aini, Nur; Widiastiani, Nindry Sulistya (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2021)
Kuliah Kerja Nyata (KKN) is a required academic activity in the curriculum of every study program at Atma Jaya University Yogyakarta with a weight of 2 credits. The implementation of KKN in the odd semester of the 2020/2021 Academic Year (KKN 78) uses the Community KKN 5.0 model without field dropping the impact of the COVID-19 pandemic. KKN started from October to November 2020. The distribution of locations KKN 78 are Kulon Progo and Gunungkidul, Yogyakarta Special Region Province. In its implementation, Units H Group 37 are located in Ngloro Village, Saptosari District, Gunungkidul. At the macro level, villages have two main potentials in the cultural and economic fields. Based on the results of observations, this village has had various training programs for the manufacture of products in the village such as food processing, in the form of cassava chips and banana chips. However, this activity has constraints on the marketing of the resulting product so it requires a marketing strategy. The purpose of KKN according to this group is to provide information on how to market processed products so that they are able to compete with other products. The compilation of KKN outcomes is carried out by collecting (secondary) data, and presenting qualitative reports that are descriptive-analysis in nature. The resulting output is a mapping of village potential which is later revealed to be e-books, pocket books and videos related to villages, village potentials and product marketing strategies.